2022
DOI: 10.3390/molecules27154830
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Differential Evaluation of Radix Bupleuri Cultivated in Different Regions Based on HPLC-MS and GC-MS Combined with Multivariate Statistical Analysis

Abstract: The quality of Radix Bupleuri is greatly affected by its growing environment. In this study, Radix Bupleuri samples that were harvested from seven different regions across northwest China were examined by high-performance liquid chromatography (HPLC) and gas chromatography (GC) coupled with mass spectrometry (MS) to reveal significant differences in quality contributed by the cultivation region. An HPLC-MS method was firstly established and used in the multiple reaction monitoring mode for the quantitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In conclusion, these data validated that the HPLC-MRM/MS method fulfilled the requirements for the quantification of saikosaponins in Radix Bupleuri. The content of saikosaponins has been shown to vary with the region where Radix Bupleuri is cultivated [20]. Therefore, in this study, North and South RB from different regions were collected and analyzed in order to reduce the influence of the growing region on the quantitative results, which is a new addition to previous reports [6,19].…”
Section: Results Of Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, these data validated that the HPLC-MRM/MS method fulfilled the requirements for the quantification of saikosaponins in Radix Bupleuri. The content of saikosaponins has been shown to vary with the region where Radix Bupleuri is cultivated [20]. Therefore, in this study, North and South RB from different regions were collected and analyzed in order to reduce the influence of the growing region on the quantitative results, which is a new addition to previous reports [6,19].…”
Section: Results Of Methods Validationmentioning
confidence: 99%
“…Compared to heat extraction, it is more convenient, more efficient, and more conducive to protecting unstable saponins from decomposition [22][23][24]. The extraction time, liquid-to-solid ratio, and ammonia concentration in the extraction solvent were optimized to maximize the concentration of derived saikosaponins, as described in a previous study [20]. The extracted saponins were detected in both positive and negative ion modes using an electrospray ionization (ESI) ion source.…”
Section: Optimization Of Extraction and Analysis Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…from different origins and the same variety, which were similar to the morphological observation results of mature plants [ 33 ]. Wang et al also proved that climatic and geographical factors affected plant growth and secondary metabolism, resulting in regional differences in the active components of Radix bupleuri [ 34 ]. These results indicated that it was not feasible to judge the variety of Radix bupleuri solely by observing the plant appearance and the content of active components.…”
Section: Discussionmentioning
confidence: 99%
“…As the main drug of CSGS, Radix Bupleuri has both evacuation and antipyretic functions, can soothe the liver and relieve depression, can lift Yang qi, and has multiple pharmacological effects, such as being antitumor, antidepression, antifibrosis, and neuroprotection [ 47 ]. Researchers extracted and analyzed the chemical components of Radix Bupleuri and found that it mainly contains saponins, volatile oils, flavonoids, polysaccharides, alkynes, and trace elements, with the saponins including saikosaponins a, saikosaponins d, saikosaponins e, and saikosaponins c [ 48 , 49 , 50 ]. Volatile oils mainly include L-ascorbyl 2, 6-dipalmitate, 2, 4-sebacedienal, alkynyl alcohol and cis, cis-9, and 12-octadecadiene-1-ol [ 51 ].…”
Section: Pharmacological Study Of Seven Herbs In Chsgmentioning
confidence: 99%